Pt-Ru decorated WO3-based photocatalyst-assisted electrolysis hybrid cell for hydrogen production - Chae, Sang Youn; Yoon, Noyoung; Mehmood, Adeel; Joo, Oh shim; Park, Eun Duck (Elsevier BV, 2025)
A photocatalyst-assisted electrolysis system, has been demonstrated to reduce energy consumption and provide stable operation for hydrogen production under intermittent light irradiation. In the photocatalyst-assisted electrolysis system cell, the photocatalyst, PtRu-WO3, stores solar energy as chemical energy via the formation of Fe3+ ions and O2 evolution during the daytime on the anolyte side; subsequently, hydrogen is produced through water electrolysis using the stored solar energy at night on the catholyte side. Simulated and natural solar energy was successfully stored by an energy-buffer system of photocatalyst/Fe2+/3+ ions for stable operation under dark conditions. Additionally, the operation of a large-scale photocatalyst-assisted electrolysis cell (light illumination area of 122.5 cm2) under natural sunlight irradiation was demonstrated. The hydrogen production efficiency was approximately -70 % higher than that of a conventional water electrolysis cell using the same electrical power.